Interação competitiva e capacidade de parasitismo de tetrastichus giffardianus (hymenoptera: eulophidae) - Silva, Bárbara Karine de Albuquerque (Universidade Federal Rural do Semi-Árido, 2021)
Biological control stands out as a viable alternative for the control of tephritids, using different species of parasitoids. The simultaneous release of parasitoids can result in the efficient control of pest tephritids, while it can also generate competitive responses due to the overlap by resources (food, host and habitat), making it essential to screen for the use of the best combinations of parasitoid species. Therefore, this study aimed to evaluate the interactions between the endoparasitoid Tetrastichus giffardianus and the ectoparasitoid Pachycrepoideus vindemmiae on the host Ceratitis capitata (Wied.) (Diptera: Tephritidae) in laboratory conditions (T = 25 ± 2 ° C, RH = 60 ± 10% and Photophase = 12h). The competition bioassays comprised two stages: In the first stage, third instar larvae of C. capitata were exposed to parasitism to T. giffardianus and P. vindemmiae, in isolation and in competition. In the second stage, pupae previously selected with the oviposition scars of T. giffardianus were exposed to P. vindemmiae and dissected at three time intervals (24, 48 and 72 hours after exposure to ectoparasitoids), to investigate the interactions inside the pupae. The results showed that P. vindemmiae predominates over T. giffardianus. The isolated T. giffardianus parasitism was greater than when this parasitoid was in competition with P. vindemmiae. The parasitism of P. vindemmiae was not affected by competition with T. giffardianus. The dissections confirmed the lethal interference that P. vindemmiae is capable of causing in the survival of T. giffardianus

Parasitoid releases for the control of fruit flies of economic importance are priorities in programs of Classic and Applied Biological Control around the world, especially for the control of Ceratitis capitata (Diptera: Tephritidae). Basic studies in laboratory and semi field conditions are essential to evaluate the efficiency of this natural enemy in order to make practical applications in the field. Therefore, the objective of this work was to evaluate the effectiveness of T. giffardianus in the parasitism of C. capitata under semi field conditions, as well as to verify the preferential foraging site, in a semiarid environment. The tests were conducted in field cages, where guava fruits infested with third instar larvae of C. capitata were exposed to parasitism of T. giffardianus in two sites (tree canopy and soil). Infested fruits not exposed to parasitism and submitted to the same experimental conditions were used as fly control. Several parameters were recorded, such as parasitism, population reduction of the fly, number of emerged parasitoids and sex ratio. Tetrastichus giffardianus showed an average general parasitism of 63.1% and was able to parasitize larvae of C. capitata both in the tree canopy and in the soil, with parasitism of 64.6 and 61.6%, respectively
Keywords: Mosca-do-mediterrâneo; Controle Biológico; Interação interespecífica; Competição intrínseca; Hiperparasitismo; Mediterranean fruit fly; Biological Control; Interspecific interaction; Intrinsic competition; Hyperparasitism; Local de forrageamento; Localização hospedeira; Parasitoide gregário; Semiárido brasileiro; Foraging site; Host location; Gregarious parasitoids; Brazilian semiarid; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA